The benefits and harms of Chinese medicinal herbs for the treatment of rapidly progressive glomerulonephritis in adult patients - LIU,Jialing (2021)
Abstract Objective The aim of this review was to assess the benefits and harms of Chinese medicinal herbs for the treatment of rapidly progressive glomerulonephritis (RPGN) in adult patients. Methods Our study included only randomized controlled trials (RCTs). We designed a strategy for searching the EMBASE, CENTRAL, PubMed, CBM, CNKI, and VIP. All studies were analyzed using the criteria of the Cochrane Handbook. All studies included were assessed the risk of bias. Review Manager ver. 5.3.5 was used for the data analysis. GRADE profiler was used to evaluate quality. Results Two studies were studied (74 Chinese participants were included). We found that compared with supportive therapies combined with specific therapies, Chinese medicinal formulae plus supportive therapies combined with specific therapies significantly reduced the serum creatinine levels (SCr; two studies, 62 participants: mean difference (MD), -145.93 μmol/L; 95% confidence interval (CI), -236.75 to –55.11; I2=0%) and utilization number of methylprednisolone and prednisone (two studies, 74 participants: MD, -1.64 g; 95% CI, -1.87 to -1.40; I2=0%). Conclusion Our study suggested that there were insufficient evidences to confirm that the use of Chinese medicinal formulae for adults with RPGN was beneficial and safe.